Katolicyzm a liberalizm. Recepcja liberalizmu na łamach współczesnej, polskiej prasy katolickiej (wybrane zagadnienia) - Tasak, Agata (Polityka i Społeczeństwo, 2021)
The subject of the analysis was the reception of liberalism in selected Polish Catholic newspapers – chosen in the context of frequently discussed differences between Polish Catholic communities. After 1989, liberalism was treated as a threat in certain Catholic communities. However, it may be assumed that the criticism concerned the liberalism understood in its stereotypical form. Liberalism was frequently and deeply criticised in “Niedziela” and “Gość Niedzielny.” It was associated with all the imperfection and evil of the contemporary world. The Catholic community related to, among others, “Tygodnik Powszechny” attempted to conduct a dialogue with representative liberal thinkers, frequently emphasising the positive aspects of the most significant liberal principles. The analysis of contemporary Polish Catholic press confirms the fact that the disputes depicted in the previous decade are still valid. Moreover, it might even be concluded that the rhetoric has sharpened and the boundaries demarcating the Catholic communities in their attitudes to liberalism have become more pronounced.